Analisa pengaruh dewan komisaris independen, komite audit independen, dan kinerja keuangan terhadap nilai perusahaan - Veny Veny; Dian Angelene; Merry Putri (President University Press, 2023)
The purposes of this study is to investigate of independent commissioners, independent audit committees, and financial performances on company value. This study was accompanied on state-owned firms listed on the IDX for the 2018-2021 period. The data are taken from the annual reports from the IDX website and each company. The research population consisted of 20 BUMN companies and several samples were occupied by the purposive sampling, so that 19 sample companies were obtained for the four observation periods (2018-2021) and a total of 58 observational data were obtained. Data is collected and processed using multiple regressions analysis. This study results shows that the independent board of commissioner has positive insignificant influence on company value, the independent audit committee does not significantly and negatively impact company value, and financial performance significantly and positively affects company value.